Tissue Conditioner Incorporating a Nano-Sized Surface Pre-Reacted Glass-Ionomer (S-PRG) Filler - Watcharapong Tonprasong (MDPI AG, 2021)
We aimed to evaluate the properties of a novel tissue conditioner containing a surface pre-reacted glass-ionomer (S-PRG) nanofiller. Tissue conditioners containing 0 (control), 2.5, 5, 10, 20, or 30 wt% S-PRG nanofiller or 10 or 20 wt% S-PRG microfiller were prepared. The S-PRG nanofillers and microfillers were observed using scanning electron microscopy. The ion release, acid buffering capacity, detail reproduction, consistency, Shore A0 hardness, surface roughness, and Candida albicans adhesion of the tissue conditioners were examined. The results indicated that the nanofiller particles were smaller and more homogeneous in size than the microfiller particles. In addition, Al, B, F, and Sr ions eluted from S-PRG were generally found to decrease after 1 day. Acid neutralization was confirmed in a concentration-dependent manner. The mechanical properties of tissue conditioners containing S-PRG nanofiller were clinically acceptable according to ISO standard 10139-1:2018, although the surface roughness increased with increasing filler content. Conditioners with 5–30 wt% nanofiller had a sublethal effect on C. albicans and reduced fungal adhesion in vitro. In summary, tissue conditioner containing at least 5 wt% S-PRG nanofiller can reduce C. albicans adhesion and has potential as an alternative soft lining material.